Knowledge, Attitude and Use of Agricultural Information as Predictors of Increased Productivity Among Small- Scale Farmers in Southwestern, Nigeria (2016)
Small scale farmers facilitate food production in order to play significant roles in stabilising economy and mitigate hunger in Nigeria. However, the level of productivity of these farmers in the South-western, Nigeria has been seemingly low; not keeping pace with the population growth rate. This trend has been partly attributed to inadequate access to or absence of agricultural information. Previous studies have concentrated more on delivery methods and the sources of agricultural information without focusing on its knowledge, attitude and use among the small scale farmers. This study, therefore, examined the extent to which knowledge, attitude and use of agricultural information predict increased productivity of small scale farmers in the South-western, Nigeria. Theories on attitude change, perception and information processing provided the framework while descriptive survey design was adopted. Oyo, Ogun and Ondo states with high yearly production index of yam, maize and cassava were purposively selected. Stratified and proportionate random sampling techniques were used in selecting 1,172 small scale farmers who are registered members of the Agricultural Development Programmes in each of the three states (Oyo-591; Ogun-479; Ondo-102). Agricultural Information Questionnaire with three sub-scales (Knowledge- r=0.72, Attitude- r=0.78 and Use- r=0.74) and Agricultural Productivity Scale (r=0.70) were used for data collection. These were complemented with six and three sessions of focus group discussion and key informant interviews with farmer‟s union executives and extension agents respectively. Data were analysed using descriptive statistics, Pearson product moment correlation and Multiple regression at 0.05 level of significance, while qualitative data were content analysed. The farmers were: male (72.1%) and female (27.9%) with a mean age of 47± 5 years; cultivating: less than 1 hectare (21.3%), 1-2 hectares (35.7%), 2-3 hectares (24.4%), 3-4 hectares (11.9%) and 4-5 hectares (6.8%). Their levels of education were: no formal education (36.6%), primary education (29.5%), secondary education (21.5%), diploma (9.9%), first degree/equivalents (2.0%) and higher degrees (6.5%). Agricultural information sought for are: technical (82.3%), economic (78.4%), socio-cultural (52.5%) and legal (8.1%); preferably sourced from: extension agents (82.5%), radio (67.2%) and fellow farmers (75.8 %). Agricultural information use (r=.73), attitude (r=.66) and knowledge (r=.56) had significant correlations with small scale farmers‟ productivity Agricultural information use (=.57), attitude (=.46) and knowledge (=.05) had significant relative contributions to farmers‟ increased productivity. There was a joint prediction of knowledge, attitude and use of agricultural information on small scale farmers‟ productivity (F(1168)=1200.71); accounting for 75.5% of its variance. Irregular visits by extension agents, poor loan access, poor radio transmission signals, and poor electricity supply were some of the constraints hindering their access to agricultural information. Dissemination of agricultural information, adoption of positive attitude and the effective use of knowledge positively influenced small scale farmers‟ productivity in the Southwestern, Nigeria. Therefore, extension agents‟ visits to small scale farmers should be regularised. Constant electricity supply, strong radio transmission signals and easy access to soft loans with low interest rates should be adequately provided.